Comparison of the Galleria baiting technique and a direct extraction method for recovering Steinernema (Nematoda: Rhabditida) infective-stage juveniles from soil - Sturhan, D; Mrácek, Z (Folia parasitologica, 2000)
Forty soil samples from forests and other biotopes in Germany and the Czech Republic were studied for the presence of entomopathogenic nematodes using the Galleria bait method at the same time as a sieving-decanting method for direct extraction of infective-stage juveniles. Five Steinernema species were recovered from the samples from Germany and four species from the samples from Czechia. All five species were recovered with both methods, but the baiting technique was generally less effective and mixtures of species were frequently undetected. The direct extraction method provided quantitative estimates of infective-stage juvenile density but no information on their infectivity or on morphological characters of adults, and nematode cultures could not be established.
Keywords: parazitologie; Life Cycle Stages; Animals; Rhabditida; zvířata; Soil; Německo; stromy; Trees; Czech Republic; Parasitology; Germany; stadia vývoje; půda; Česká republika